2013
DOI: 10.5777/ambiencia.2013.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Influência do armazenamento na qualidade fisiológica de sementes de soja tratadas com inseticidas / Influence of storage on thephysiological qualityof soybean seeds treated with insecticides

Abstract: ResumoA utilização de inseticidas no tratamento de sementes cresce a cada safra em decorrência do ataque progressivo de diferentes espécies de insetos-pragas. O objetivo deste trabalho foi avaliar a influência do fipronil e tiametoxam no desempenho fisiológico das sementes de soja sob armazenamento. O delineamento experimental utilizado foi inteiramente casualizado com quatro repetições, distribuído em esquema fatorial (4 x 3 x 2), utilizou-se quatro cultivares (BMX MAGNA RR, BMX Potência RR, NK 3358 RR e NK 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…In this process, technical and logistical matters determine that seeds be treated before being packed and then stored up to the time of sowing (Brzezinski et al, 2015;Santos et al, 2018). However, storage of treated seeds can have some unintended consequences, such as possible detrimental effects from the chemical products on the seeds, as reported for some molecules by Dan et al (2010), Piccinin et al (2013), Ferreira et al (2016) and Santos et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, technical and logistical matters determine that seeds be treated before being packed and then stored up to the time of sowing (Brzezinski et al, 2015;Santos et al, 2018). However, storage of treated seeds can have some unintended consequences, such as possible detrimental effects from the chemical products on the seeds, as reported for some molecules by Dan et al (2010), Piccinin et al (2013), Ferreira et al (2016) and Santos et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had shown that the application of the insecticide thiamethoxan negatively affect the physiological quality of seed (Castro et al, 2008;Piccinin et al, 2013). In this study, no significant difference regarding to seed vigor was observed from the noninoculated and non-treated control when only thiamethoxan was applied to the pre-inoculated seeds even after 51 days of storage (Table 3).…”
Section: Physiological Quality Of Seedmentioning
confidence: 46%
“…Nevertheless, industrial seed treatments still face many challenges that need to be addressed regarding the storage period of the seed and the compatibility of agrochemicals with inoculants. Previous studies demonstrated that seed treatment with fungicides and insecticides (Pereira et al, 2010a;Dan et al, 2012;Ferreira et al, 2016;Camilo et al, 2017) as well as the period of storage (Krohn and Malavasi, 2004;Dan et al, 2010;Piccinin et al, 2013) can have negative effects on physiological quality of soybean seed. As a result, seed with low vigor can decrease seedling emergence (Khaliliaqdam et al, 2012) and reduce yield (Scheeren et al, 2010), which could seriously lead to unfeasibility of industrial seed treatments.…”
mentioning
confidence: 99%
“…For the effect of storage period (Figure 1D), our results were in agreement with those of De Moraes Dan et al (2013), who found that in soybean seeds treated with the insecticide thiamethoxam, seed vigor was drastically reduced by a storage period of 90 days. In another study, Piccinin et al (2013) also found that soybean seeds treated with the insecticides fipronil and thiamethoxam affected the vigor of seeds exposed to storage for 180 days under natural conditions.…”
Section: Resultsmentioning
confidence: 90%